Angiotensin I-Converting Enzyme Inhibitory Peptides of Chia (Salvia hispanica) Produced by Enzymatic Hydrolysis - Maira Rubi Segura Campos; Fanny Peralta González; Luis Chel Guerrero; David Betancur Ancona (International Journal of Food Science)
Synthetic angiotensin I-converting enzyme (ACE-I) inhibitors can have undesirable side effects, while natural inhibitors have no side effects and are potential nutraceuticals. A protein-rich fraction from chia (Salvia hispanica L.) seed was hydrolyzed with an Alcalase-Flavourzyme sequential system and the hydrolysate ultrafiltered through four molecular weight cut-off membranes (1 kDa, 3 kDa, 5 kDa, and 10 kDa). ACE-I inhibitory activity was quantified in the hydrolysate and ultrafiltered fractions. The hydrolysate was extensive (DH = 51.64%) and had 58.46% ACE-inhibitory activity. Inhibition ranged from 53.84% to 69.31% in the five ultrafiltered fractions and was highest in the <1 kDa fraction (69.31%). This fraction’s amino acid composition was identified and then it was purified by gel filtration chromatography and ACE-I inhibition measured in the purified fractions. Amino acid composition suggested that hydrophobic residues contributed substantially to chia peptide ACE-I inhibitory strength, probably by blocking angiotensin II production. Inhibitory activity ranged from 48.41% to 62.58% in the purified fractions, but fraction F1 (1.5–2.5 kDa) exhibited the highest inhibition (IC50 = 3.97 μg/mL; 427–455 mL elution volume). The results point out the possibility of obtaining bioactive peptides from chia proteins by means of a controlled protein hydrolysis using Alcalase-Flavourzyme sequentional system.